Salmonella Prevalence Varies Over Time and Space in Three Large, Adjacent Cattle Operations in the Southwestern United States - Hanson, Devin L.; Loneragan, Guy H.; Brown, Tyson R.; Edrington, Tom S. (Frontiers in Animal Science, 2022)
We set out to describe the prevalence of Salmonella enterica in three large, adjacent cattle operations in the southern High Plains of the United States. Operations included two dairies (one of which routinely administers a commercially available Salmonella vaccine) and one feedlot. Samples were collected monthly for 12 months. At each sample collection, 25 freshly voided fecal pats and a sample from each of the water troughs were collected from each of five pens of cattle within an operation. Each monthly collection included a total of 375 fecal and approximately 32 water samples for a yearly total of 4,500 and 379 samples, respectively (note that the number of water troughs per pen varied within an operation). Salmonella was commonly recovered from fecal (71.3%) and water (28.5%) samples and tended to follow somewhat similar temporal patterns over time. However, its prevalence varied among operations despite being adjacent properties in that Salmonella was recovered from 61.3, 80.1, and 75% of fecal samples from dairy 1, dairy 2 and the feedlot, respectively. Salmonella prevalence in water samples across collection times averaged 36.1, 70.2, and 46.1% for dairy 1, dairy 2, and the feedlot, respectively. While it is uncertain why the Salmonella prevalence varied from operation to operation, the higher observed prevalence of Salmonella in water on dairy 2 and/or the use of a commercial Salmonella vaccine by dairy 1 may offer a partial explanation.